Membudayakan Magrib Mengaji di Desa Tamiang - Amru Hasibuan; Akhir Saleh Pulungan; Ismail Nasution; Kali Junjung Hasibuan; Fitri Yani Nasution; Dina Kumala Sari; Nuratizah Siregar; Nursamunah Pasaribu; Milda Sartika Hasibuan (Jurnal Transformasi Pendidikan Indonesia, 2025)
The habit of reading the Qur'an at Maghrib prayer is one of the efforts to shape a young generation with noble morals and strong religious knowledge. However, in the region, this tradition is starting to diminish due to technological developments, lack of parental attention and minimal religious activities for children. Community service activities with the theme "cultivating Maghrib Quran reading" were carried out in Tamiang Village, Batang Lubu Sutam District, Padang Lawas Regency as a form of education and religious guidance for children and adolescents. The goal is to revitalize interest in reading the Qur'an at Maghrib prayer, familiarize positive interactions between Quran teachers and children in Tamiang Village and strengthen the role of families and communities in fostering the morals of the younger generation. Implementation methods include direct coaching, mentoring Quran learning, and routine habits of reading the Qur'an after congregational Maghrib prayers. This activity involves Quran teachers, children and the local community.  As a result, the religious atmosphere in the village has become more vibrant, children are more focused in how they spend their evening prayers, and social relationships have been strengthened among residents.